Decision Support System Feasibility Lending At KSU Mitra Karya Cooperative Customer Unit XXVIII with Analytical Hierarchy Process Method: Decision Support System Feasibility Lending At KSU Mitra Karya Cooperative Customer Unit XXVIII with Analytical Hierarchy Process Method - Temasokhi Ndruru; Fristi Riandari (Institute of Computer Science (IOCS), 2019)
Decision Support System (DSS) is a system that can assist a person in making accurate decisions and targeted. Many problems can be solved by using CMS, one of which is determining the feasibility of a credit recipient customers. There are several methods that can be used in building a CMS one of them is the Analytical Hierarchy Process (AHP). AHP is yan method most widely used in solving problems that are multiple criteria, such as the eligibility determination SPK customer credit recipients. This study using AHP in determining credit worthiness recipient customers on Business Multipurpose Cooperative Unit of Work Partners XXVIII. In determining the credit worthiness of customers receiver, there are several criteria on which to base decisions, among others Dwelling, Income, dependents, and The work. The end result of this research is the result of global priority customer criteria, sorted from highest to lowest, so the cooperative can easily make decisions by looking at the results.